Belajar Public Speaking sebagai Komunikasi Efektif di Sekolah Dasar - Wahdiat, Irwan Sutirman; Hannagara, Haidar Ahmad; Rahman, Rezaldy Al; Pratamana, Febri Aji; Farhan, Muhammad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Students still do not fully possess public speaking skills. This reluctance to appear in front of the public is due to low self-confidence and lack of mastery of public speaking techniques. The aim of this research is to analyze the effectiveness of speaking as an important communication skill and to identify learning strategies that can improve speaking skills in various real-life situations, including academically, professionally, and socially. However, many people have difficulty or are afraid of speaking in public, which makes them unable to communicate effectively. so you have to take communication training. The education team determined SD Negeri 1, 2, and 3 Karang Bloom as locations for public speaking training. Educational activities at SD 1, 2, and 3 Karang Bloom, will be held on 19-21 August 2024. Starting at 08.00-11.00 WIB, participants have gathered in their respective classes. Participants numbering approximately 25 students (coming from grades 4, 5 and 6) took part in the activities in an orderly manner and were accompanied by an educational team from Gunung Jati Swadaya University students. The first activity started with an ice breaker after which the material was provided.